THE INFLUENCE OF GAS COMPOSITION ON THE RESPIRATION RATE OF BANANA (Var. Janten) ON MODIFIED ATMOSPHERE STORAGE - Tito Yasin; Rofandi Hartanto; Agus Haryano; Tamrin . (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Respiration rate was generally used as an indicator of the rate of metabolism for agricultural comodities.  The research aimed to determine the influence of gas composition to respiration rate and the changes of total acid, sweetness level and hardness level of banana (var. Janten) that was storaged at two different temperatures (room temperature (29 oC) and cold temperature(15 oC)).  This research was conducted by modifying the gas composition(O2, CO2, and N2) in the storage jar.  The results showed that respiration rate of banana tended to increase with time at both temperatures.  Total acid declined steadily at room temperature but fluctuated at cold temperature.  Sweetness level showed an increase and the hardness level showed a decrease with time at both temperatures during the storage process.  Modified atmosphere was able to extend shelf life of banana to 12 days at room temperature and 26 days at cold temperature.  The best gas composition for banana (var. Janten) was 4% O2, 5% CO2, and 91 % N2 (by volume). Keywords:Modified Atmosphere, Gas Composition, Respiration Rate, Total Acid, Sweetness Level, Hardness Level .